A dynamic reversible phenylboronic acid sensor for real-time determination of protein–carbohydrate interactions on living cancer cells. Issue 99 (29th November 2022) - Song, Quanquan; Li, Qian; Chao, Shuang; Chen, Xian; Li, Ronghui; Lu, Yuchao; Aastrup, Teodor; Pei, Zhichao
Abstract : A dynamic reversible phenylboronic acid sensor for real-time determination of protein–carbohydrate interactions on living cancer cells. Abstract : Real-time detection of glycosylation on label-free cancer cell surfaces is of significance for the diagnosis and treatment of cancer. In this work, we have successfully developed a novel dynamic reversible sensor based on pH-sensitive phenylboronic esters to determine in real-time the binding kinetics of protein–carbohydrate interactions on suspension cancer cell surfaces using a quartz crystal microbalance (QCM) technique.